Geological controls on shallow gas distribution and seafloor seepage in an Arctic fjord of Spitsbergen, Norway. (September 2019) - Roy, Srikumar; Senger, Kim; Hovland, Martin; Römer, Miriam; Braathen, Alvar
Abstract: This study integrates high-resolution shallow- and deep-geophysical datasets to study the seabed seepage systems linked to subsurface shallow gas and geological features influencing the fluid flow in Nordfjorden, central Spitsbergen (Arctic Norway). This is one of the tributary fjords of the Isfjorden fjord system in Spitsbergen which has the highest density of pockmarks ranging up to 20/km 2 . The 535 pockmarks identified manually in the 300 km 2 large study area have diameters ranging from 10 m to 212 m, and depth varying between 1 m and 8 m. Sub-surface seep-related acoustic features such as, enhanced reflections, acoustic blanking and turbidity zones recorded on 55 km of new high-resolution sub-bottom acoustic data suggest shallow gas (free and/or dissolved) occurrences in the marine sediments beneath the pockmarks. Structural features (thrust faults and associated folds) belonging to the Palaeogene West Spitsbergen fold-and-thrust belt and Early Cretaceous igneous sills have been interpreted on 2D multichannel seismic data, in the Triassic and Permian successions. Some of these faults and igneous sills form seafloor ridges, where pockmark density is high, and they are typically aligned. Acoustic flares attributed to active gas seepage from the seafloor were imaged in the water column in the southern part of Nordfjorden, above the sub-surface shallow gas occurrences and thrust faults. The integrated analysis of these geophysical datasets suggests that the near-seafloor tectonically deformed stratum plays an important role in the up-dip propagation of fluids (liquids and/or gas), distribution of shallow gas in marine sediments, and seepage at the seafloor. Highlights: Identification of 535 pockmarks in Nordfjorden, an Arctic fjord in central Spitsbergen. Characterisation of seep-related acoustic features in a central Spitsbergen fjord. Correlation of seabed morphological features with sub-surface tectonic features. Tectonic features and igneous sills facilitate fluid flow and seepage. Gas flares in the water column near sub-cropping thrust faults indicate local active seepage.